The Effectiveness of the Implementaton of Blended Learning in Economics - Samudra Wiryantama; Albrian Fiky Prakoso (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This research aims to compare the effectiveness of blended learning and online learning in influencing students’ learning outcomes, as well as the effectiveness of blended learning application based on the students’ learning outcomes, learning activities, and student responses in central bank, payment systems, and payment instruments chapter. This is a quasi-experimental study with a non-equivalent control group design. The sample used in this research consisted of 68 students from class X IPS 1 and X IPS 3 of SMAN 1 Porong 2020-2021. The data used in this study were obtained using tests, questionnaires, and observations which were analyzed using non-parametric statistical analysis, N-gain calculation, and descriptive statistical analysis. The results showed that (1) learning models affect student learning outcomes; (2) there is a significant difference in the average students’ learning outcomes between blended learning and online learning, (3) blended learning is more effective to be implemented than online learning, based on the students’ learning outcome, and (4) blended learning is effective to be implemented based on learning outcomes, activities, and student responses.